Comparison of the Fractional Exhaled Nitric Oxide Levels in Adolescents at Three Schools Located Three Different Distances from a Large Steel Mill - Murat Acat; Yusuf Aydemir; Onur Yazıcı; Mahmut Turğut; Mustafa Çörtük; Murat Çakar; Zehra Yaşar; Sami Deniz; Erdoğan Çetinkaya (Canadian Respiratory Journal)
Objectives. Exposure to ambient metals and air pollutants in urban environments has been associated with impaired lung health and inflammation in the lungs. Fractional exhaled nitric oxide (FeNO) is a reliable marker of airway inflammation. In this study, we aimed to compare the FeNO levels of three schools that have different distances from iron and steel industry zone for assessing the effects of heavy metals and air pollution on their respiratory health. Methods. Pulmonary function test and FeNO measurements were evaluated in 387 adolescents in three schools which have different distance from plant. Results. FeNO levels were significantly higher in School I (n=142; 18.89±12.3 ppb) and School II (n=131; 17.68±7.7 ppb) than School III (n=114; 4.28±3.9 ppb). Increased FeNO concentration was related to the distance of iron and steel industry zone in young adults. Conclusion. The FeNO concentrations in school children were inversely proportional to the distance from the steel mill. There are needed some studies that can evaluate the safe distance and legislation must consider these findings.